2008
DOI: 10.1007/s00296-008-0591-y
|View full text |Cite
|
Sign up to set email alerts
|

Are individuals with severe haemophilia A prone to reduced bone density?

Abstract: Individuals with severe haemophilia A may be at risk for reduced bone mineral density because of reduced weight-bearing exercise and hepatitis C infection. For confirming the reduced bone density, in the current cross-sectional study, we tried to address bone mineral density in individuals with severe haemophilia A and surveyed the relation of reduced bone density with hepatitis C viruses. To fulfil these aims, bone density and biochemical indexes in 18 individuals with severe haemophilia A and also in 18 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 7 publications
0
33
0
6
Order By: Relevance
“…Hepatitis C has been cited as a potential risk factor but the results are conflicting, with some studies supporting the association [11,13,14,20] and others not [1,21,24,27]. This study demonstrated that patients with a history of HCV had lower BMD at the hip than non-affected patients, and that a history of HCV was an independent predictor for reduced BMD at the femoral neck.…”
Section: Discussionmentioning
confidence: 60%
“…Hepatitis C has been cited as a potential risk factor but the results are conflicting, with some studies supporting the association [11,13,14,20] and others not [1,21,24,27]. This study demonstrated that patients with a history of HCV had lower BMD at the hip than non-affected patients, and that a history of HCV was an independent predictor for reduced BMD at the femoral neck.…”
Section: Discussionmentioning
confidence: 60%
“…These findings were confirmed in a study by Mansouritorghabeh et al. [32]. Weight‐bearing physical activity (sports), physical therapy, surgery to remobilize patients, and calcium and vitamin D supplementation are recommended [33].…”
Section: Haemophilic Arthropathymentioning
confidence: 69%
“…The interleukin 1 (IL-1) and tumour necrosis factor-alpha (TNF-) which are mediator of inXammation may encourage RANK-L production via T-cells [7]. HCV can inXuence peak bone mass by causing abnormalities in metabolisms of vitamin D and testosterone, so several studies with higher patients number could show correlation between HCV and RBD, [7,12] while some other surveys could not establish this concept mostly due to low numbers of patients entered the studies [4,5,13].…”
Section: Pathogenesis Of Reduced Bone Densitymentioning
confidence: 97%
“…Bone mass status is the result of equilibrium between bone mass gaining during childhood period and bone loss during adulthood. So it is highly important to obtain suYcient bone mass during childhood [4]. It has been demonstrated that individuals with higher bone mass at the end of adolescence have higher protection against the gradual decrease in bone mass during ageing [5,6].…”
Section: Introductionmentioning
confidence: 99%